Futures consciousness and governance transitions for climate adaptation in South African protected areas - Claudia Munera-Roldan (Ecosystems and People, 2023)
ABSTRACTIn the context of climate change, protected areas play an important role in implementing the Sustainable Development Goals and addressing resource nexus challenges. However, setting protected areas for long-term conservation is often criticised for using narratives based on political, economic, and scientific assumptions to justify which elements of nature should be conserved and what actions should be implemented, creating a sense that conservation outcomes are desirable and universally accepted. Such narratives exclude other voices, values, and practices, limiting alternative options for the future. Adapting protected areas to climate change requires innovative approaches to address societal challenges and critically examining conservation strategies to make informed decisions under scenarios of change. This article presents the case of the Garden Route National Park in South Africa and the approach used to co-create inclusive visions of the future with local stakeholders. I draw on theoretical insights and empirical data collected through interviews with the park staff to describe the use of futures consciousness as an approach to understanding how people perceive change, prepare for, and embrace the future. I explore how people’s perceptions of change mobilize action to address complex problems and create alternative imaginaries beyond spatial and temporal boundaries. Futures consciousness can contribute to understanding processes that enable or constrain transformation and identifying options for mobilising change towards desired future goals. The findings can help managers examine individual and collective assumptions about adaptation, inform future-oriented practices and advance opportunities for transformational change to build resilient, just futures for nature and people.